IMPLEMENTATION OF OCCUPATIONAL SAFETY AND HEALTH FOR USING SEA TRANSPORTATION (CASE STUDY AT TENGKAYU II PORT OF TARAKAN CITY) - Kresna Febriyanto; Suprayitno Suprayitno (Universitas Muhammadiyah Kalimantan Timur, 2019)
All sea transportation facilities users in the world in general especially in Indonesia always prioritize safety, security and comfort aspects. The ship accidents such as sinking, burning, etc., are problems related to the safety and security of sea transportation.The purpose of this study it was to determine the application of occupational safetyand health inside the speedboat accordance with Ministerial Regulation No. 6 of 2018 concerning Occupational Safety and Health (OSH) in the Ministry of Maritime Affairs and Fisheries.This study used a qualitative method carried out at the port of Tengkayu II, Tarakan City, North Kalimantan were speedboat passengers as the main informants, as well as Transportation Service officers and dock workers as supporting informants.The sampling technique used accidental sampling technique. The results of the study stated that the application of OSH inside the speedboat had not been fully implemented.Passenger awareness is a fundamental cause of the non-implementation of that regulations. One aspect of applying OSH inside the speedboat in accordance with applicable regulations is to use a life jackets while in a speedboat. Passengers only wear life jackets just before leaving when inspected by officers, but will be removed if it is far from the port. Discomfort factor is the main reason why life jackets are not used. In addition, the boat captain's negligence was still found because it did not prioritize the safety of the feeder, and driving was not in accordance with the applicable standard operating procedures.